Identifying opportunities to advance health equity in interventional cardiology: Structural heart disease. Issue 4 (27th November 2021) - Allana, Salman S.; Alkhouli, Mohamad; Alli, Olueseun; Coylewright, Megan; Horne, Aaron; Ijioma, Nkechi; Kadavath, Sabeeda; Pineda, Andres M.; Sanchez, Carlos; Schreiber, Theodore L.; Shah, Atman P.; Smith, Conrad; et al.
Abstract: Health care practices are influenced by variety of factors. These factors that include social determinants, race and ethnicity, and gender not only affect access to health care but can also affect quality of care and patient outcomes. These are a source of health care disparities. This article acknowledges that these disparities exist in getting optimal care in structural heart disease, reviews the literature and proposes steps that can help reduce these disparities on personal and committee levels.